Association between self-administrated prophylactics and SARS-CoV-2 infection among traditional market vendors from the Central Highlands of Peru: A nested case-control study - Daniel A. Andrade; Ana Ho-Palma; Cesar A. Valdivia-Carrera; Astrid Munguia; Christine Leyns; Javier Guitian; Eloy Gonzales-Gustavson (PLoS ONE, 2025)
Although COVID-19 is no longer a public health emergency of international concern, understanding behaviours such as self-medication remains relevant for informing future outbreak responses and improving public health preparedness. Despite its widespread use during the pandemic, research on medications preventing SARS-CoV-2 infection in healthy individuals is scarce. We investigated the association between self-administered prophylactics and SARS-CoV-2 infection during the third wave of the pandemic in Peru. A nested case-control study was carried out in a cohort of traditional market vendors in the Peruvian Central Highlands, enrolled in a health program. Cases (positive SARS-CoV-2 diagnosis) were matched with controls (negative) by age, sex, and market of origin. Conditional logistic regression models were fitted to evaluate the association between self-administered prophylactics and SARS-CoV-2 infection. As a result, 73 cases were matched with 176 controls. Acetylsalicylic acid consumption increased SARS-CoV-2 infection odds (adjusted Odds Ratio 2.34; 95% Confidence Interval 1.17–4.66). Conversely, vitamin C consumption reduced infection odds (adjusted Odds Ratio 0.44; 95% Confidence Interval 0.23–0.87). Finally, not having the COVID-19 booster increased infection odds (adjusted Odds Ratio 3.38; 95% Confidence Interval 1.43–7.95). In conclusion, our findings suggest that acetylsalicylic acid consumption increased the odds of SARS-CoV-2 infection, whereas vitamin C consumption decreased the infection odds during the third epidemic wave in Peru. Further research on the use of these medications is needed to establish a robust causal relationship with SARS-CoV-2 infection.